THROMBOLYTIC THERAPY IN PATIENTS WITH MYOCARDIAL INFARCTION - G. P. Ishmurzin; A. A. Podolskaya; A. V. Bondarev A.V (Российский кардиологический журнал)
Acute myocardial infarction (AMI) is the leading cause of mortality in the most countries, including the Russian Federation. AMI is caused by rupture or erosion of atherosclerotic plaque, followed by occlusive coronary thrombosis. Thrombolytic therapy (TLT) is one of the most widely used and accessible pharmaceutical methods for treating recent thrombosis-related coronary occlusion. Many international multi-centre randomized studies, including tens of thousands participants worldwide, have demonstrated high effectiveness and excellent success rates for systemic TLT in AMI patients. The importance of early TLT has been emphasized (GISSI I, 1986; ISIS 2, 1988; AIMS, 1990; GUSTO I8 III, 1993–1997). Early TLT has beneficial effects on myocardial electric stability and prevents hemodynamic complications and remodelling, therefore, reducing the risk of disability and mortality.